1993
DOI: 10.1001/archpsyc.1993.01820180046005
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Rapid vs Gradual Discontinuation of Lithium Treatment in Bipolar Disorders

Abstract: Risk of early recurrence of BP disorder following discontinuation of lithium maintenance is elevated, but may be both predictable (timing and polarity) and modifiable by gradual discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
0
5

Year Published

1995
1995
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(134 citation statements)
references
References 37 publications
11
118
0
5
Order By: Relevance
“…Risks were similar with both BD I and II subtypes, but significantly higher for women with a history of 4 or more prior episodes and for women who abruptly or rapidly (< 2 weeks) discontinued lithium treatment proximate to conception. These findings are consistent with the view that either pregnancy may have little effect on recurrence risk in BD or discontinuation of maintenance treatment itself represents a major, and perhaps dominant, stressor (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Pregnancy and Recurrence Risk In Bdsupporting
confidence: 85%
“…Risks were similar with both BD I and II subtypes, but significantly higher for women with a history of 4 or more prior episodes and for women who abruptly or rapidly (< 2 weeks) discontinued lithium treatment proximate to conception. These findings are consistent with the view that either pregnancy may have little effect on recurrence risk in BD or discontinuation of maintenance treatment itself represents a major, and perhaps dominant, stressor (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Pregnancy and Recurrence Risk In Bdsupporting
confidence: 85%
“…Unrecognized treatment non‐adherence can lead physicians to believe that the patient is non‐responsive, resulting in unnecessary dose increases (especially problematic for drugs with a narrow therapeutic index), medication switches, or adjunctive medications 341. Treatment withdrawal may precipitate recurrence; 50%‐90% of patients discontinuing lithium experience a recurrence within 3‐5 months,345, 346 with rapid lithium discontinuation associated with greater recurrence risk than gradual discontinuation 347. Withdrawal of other mood stabilizers also predicts recurrence 348, 349.…”
Section: Maintenance Therapy For Bipolar Disordermentioning
confidence: 99%
“…6 The clinical efficacy of lithium in preventing recurrent affective episodes requires a lag period for onset and is reversed upon discontinuation of treatment only after weeks or months. [7][8][9] By virtue of its prophylactic properties, lithium is thought to target the underlying pathophysiology of the disease, yet the precise molecular mechanism for this therapeutic action remains elusive. Evidence from both in vitro and in vivo studies has demonstrated that lithium exerts multiple effects on neurotransmitter/receptor-mediated signaling, ion transport, signal transduction cascades, hormonal and circadian regulation, and profoundly alters gene expression patterns (see reviews Lenox and Hahn, 3 Lenox et al, 10 Manji and Lenox, 11 Jope, 12 Williams and Harwood, 13 and Manji and Lenox 14 ).…”
Section: Introductionmentioning
confidence: 99%